Treatment management of haematological malignancies in people living with HIV. Issue 9 (September 2020) - Re, Alessandro; Cattaneo, Chiara; Montoto, Silvia
Summary: Although the incidence of HIV-associated lymphomas decreased after the introduction of effective combination antiretroviral therapy, they became the most common AIDS-related cancer in high-income countries. Moreover, as people living with HIV live longer, a wide range of non-AIDS-related cancer has emerged, including other haematological malignancies. Nonetheless, combination antiretroviral therapy has offered people with HIV the opportunity to receive the same therapies as those provided to the general population, and intensive curative therapies have become the standard. However, several population-based studies highlight a major health-care disparity between people with HIV and those without, with people who are HIV positive often excluded from using innovative therapies and participating in prospective trials. In addition, patients from low-income countries frequently receive inappropriate treatment. The hope is that with increased awareness of effective curative options these disparities will decrease, and people with HIV will be given the same therapeutic opportunities and enrolled in clinical trials alongside patients who are HIV negative.